Inhaled Drug Delivery: A Practical Guide to Prescribing Inhaler Devices - Pierre Ernst (Canadian Respiratory Journal)
Direct delivery of medication to the target organ results in a high ratio of local to systemic bioavailability and has made aerosol delivery of respiratory medication the route of choice for the treatment of obstructive lung diseases. The most commonly prescribed device is the pressurized metered dose inhaler (pMDI); its major drawback is the requirement that inspiration and actuation of the device be well coordinated. Other requirements for effective drug delivery include an optimal inspiratory flow, a full inspiration from functional residual capacity and a breath hold of at least 6 s. Available pMDIs are to be gradually phased out due to their use of atmospheric ozone-depleting chlorofluorocarbons (CFCs) as propellants. Newer pMDI devices using non-CFC propellants are available; preliminary experience suggests these devices greatly increase systemic bioavailability of inhaled corticosteroids. The newer multidose dry powder inhalation devices (DPIs) are breath actuated, thus facilitating coordination with inspiration, and contain fewer ingredients. Furthermore, drug delivery is adequate even at low inspired flows, making their use appropriate in almost all situations. Equivalence of dosing among different devices for inhaled corticosteroids will remain imprecise, requiring the physician to adjust the dose of medication to the lowest dose that provides adequate control of asthma. Asthma education will be needed to instruct patients on the effective use of the numerous inhalation devices available.